Write the equation a = bc in logarithmic form.

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

It is given that a = b*c.

Take the logarithm to any base B of both the sides.

`log_B a = log_B(b*c)`

Use the property `log_B a*b = log_B a + log_B b`

=> `log_B a = log_B b + log_B c`

The given relation is equivalent to `log_B a = log_B b + log_B c`

We’ve answered 319,823 questions. We can answer yours, too.

Ask a question